THE INFLUENCE OF PERCEIVED QUALITY OF SERVICE ON PATIENT LOYALTY IN THE OUTPATIENT INSTALLATION OF PUSPA HUSADA HOSPITAL IN 2023 - Azzahra, Dhannisa; Prapanca, Yuli; Nurminingsih (Transpublika Publisher, 2023)
In the era of Industry 4.0, hospitals (RS) must establish enduring patient relationships to thrive. This poses a challenge for RS Puspa Husada due to intensifying competition among hospitals offering diverse advancements in healthcare services. The focus is on enhancing service quality to foster patient loyalty. This study aims to assess the impact of service quality on patient loyalty, employing a quantitative, cross-sectional research design. The investigation was conducted at RS Puspa Husada between June and July 2023. The study encompassed a population of 338 patients over three months, averaging 113 patients per month. Utilizing a saturated sampling technique, the entire population was included as the research sample. The research instrument involved a closed-ended questionnaire featuring a response scale (via checklist completion). Logical regression analysis was employed as the research analysis method to evaluate the influence of research variables. Research findings indicated that the physical evidence variable showed sig-p of 0.041, reliability had sig-p of 0.006, empathy demonstrated sig-p of 0.037, responsiveness displayed sig-p of 0.046, and guarantee presented sig-p of 0.018. The research concludes that a significant impact exists between the quality of service variables—physical evidence, reliability, empathy, responsiveness, and guarantee—on patient loyalty. Among these factors, service reliability emerges as the primary influencer of patient loyalty within the Outpatient Department of RS Puspa Husada.